Ask a New Question
Search
Question Use the polynomial identity (x^2+y^2)^2=(x^2−y^2)^2+(2xy)^2 to generate a Pythagorean
Question
Use the polynomial identity (x^2+y^2)^2=(x^2−y^2)^2+(2xy)^2 to generate a Pythagorean triple when x equals 7 and y
2 answers
92 views
use the polynomial identity (x^2+y^2)^2=(x^2-y^2)^2 +(2xy)^2 to generate a Pythagorean triple where x=7 and y=4
0 answers
4 views
Ashley wants to generate a Pythagorean triple when x = 18 and y = 9 using the polynomial identity (x2+y2)2 = (x2−y2)2+(2xy)2 .
1 answer
7 views
Ashley wants to generate a Pythagorean triple when x = 11 and y = 4 using the polynomial identity (x2+y2)2 = (x2−y2)2+(2xy)2 .
1 answer
6 views
Mei wants to generate a Pythagorean triple when x equals 8 and y equals 6 using the polynomial identity
1 answer
asked by
jim
31 views
Use the polynomial identity (x2+y2)2=(x2−y2)2+(2xy)2
to generate a Pythagorean triple when x equals 7 and y equals 4. Write the
1 answer
asked by
jim
44 views
Jamar wants to generate a Pythagorean triple when x equals 12 and y equals 9 using the polynomial identity
1 answer
20 views
Jamar wants to generate a Pythagorean triple when x equals 12 and y equals 9 using the polynomial identity
1 answer
asked by
burnout
16 views
Jamar wants to generate a Pythagorean triple when x equals 12 and y equals 9 using the polynomial identity
1 answer
asked by
hudson
46 views
Jamar wants to generate a Pythagorean triple when x equals 12 and y equals 9 using the polynomial identity
1 answer
57 views